One-Pot Enzymatic Production of Lignin-Composites - Ion, Sabina; Opris, Cristina; Cojocaru, Bogdan; Tudorache, Madalina; Zgura, Irina; Galca, Aurelian C.; Bodescu, Adina M.; Enache, Madalin; Maria, Gabriel-Mihai; Parvulescu, Vasile I. (Frontiers in Chemistry, 2018)
A novel and efficient one-pot system for green production of artificial lignin bio-composites has been developed. Monolignols such as sinapyl (SA) and coniferyl (CA) alcohols were linked together with caffeic acid (CafAc) affording a polymeric network similar with natural lignin. The interaction of the dissolved SA/CA with CafAc already bound on a solid support (SC2/SC6-CafAc) allowed the attachment of the polymeric product direct on the support surface (SC2/SC6-CafAc-L1 and SC2/SC6-CafAc-L2, from CA and SA, respectively). Accordingly, this procedure offers the advantage of a simultaneous polymer production and deposition. Chemically, oxi-copolymerization of phenolic derivatives (SA/CA and CAfAc) was performed with H2O2 as oxidation reagent using peroxidase enzyme (2-1B mutant of versatile peroxidase from Pleurotus eryngii) as catalyst. The system performance reached a maximum of conversion for SA and CA of 71.1 and 49.8 %, respectively. The conversion is affected by the system polarity as resulted from the addition of a co-solvent (e.g. MeOH, EtOH or THF). The chemical structure, morphology, and properties of the bio-composites surface were investigated using different techniques, e.g. FTIR, TPD-NH3, TGA, contact angle and SEM. Thus, it was demonstrated that the SA monolignol favored bio-composites with a dense polymeric surface, high acidity and low hydrophobicity, while CA allowed the production of thinner polymeric layers with high hydrophobicity.